Dinamika Psikologi Bekerja dalam Lingkungan Ekstrim dengan Ketidakpastian yang Tinggi - Perwira, Luqman Tifa; Syuhada, Muhammad Nur (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Teams that work to respond to disaster situations or other safety threats are faced with high risks that can affect other people and themselves. The Gegana Troop is a form of team that works to handle crisis situations. This unit, which is under the command of the Brimob Unit at POLRI Headquarters, has the main function of taking action against high-level and high-intensity social security and order disturbances, especially organized crime that uses firearms and/or explosives. These officers face huge consequences if mistakes occur in the tasks they carry out. This situation certainly has a huge psychological impact on the officers. This research aims to reveal the psychological dynamics of individuals who work in extreme situations with very high uncertainty through qualitative methods with a phenomenological approach. There are three main findings, namely forms of uncertainty, the psychological impact of uncertainty, and efforts to deal with uncertainty. The findings from this research can be used as study material for policy makers to be able to carry out the necessary series of prevention or interventions, not only to optimize their tasks in the field, but also to overcome potential problems that could arise from these tasks.